Comparison of Surgically Induced Corneal Astigmatism in Cataract Patients after Phacoemulsification Versus Manual Small-Incision Cataract Surgery - Giyathaldeen T. Neameh1, Mohammed Qasim Al Nuwaini1, Hayder M. M. Al-Talqani2, Mohammed Qasim Al Nuw (Institute of Medico-legal Publications Pvt Ltd, 2020)
The advances in cataract surgery are aimed at finding a surgical method capable of providing accurate andpredictable results in terms of outcome. Surgically Induced Astigmatism (SIA) is one of the causes of the poorquality of vision post-operatively because of the blurring of images. SIA in turn, depends on the type, lengthand the position of the incision.so this study to compare the mean keratometeric reading preoperative andone month postoperative in phacoemulsification versus manual small-incision cataract surgery and to findwhich produce less surgically induced astigmatism. This was a prospective, observational, cohort study onpatient with cataract carried out from April 2018 to September 2018. This study conducted on (206) patientsattending to ophthalmic department in Najaf. The cases were divided into two groups. Each group had 103patients. One group had undergone phacoemulsification and the other group had undergone superior scleraltunnel incision and follow up after one month to find which procedure less surgically induced astigmatism.Preoperative and postoperative keratometeric was performed after one month. According to this study meankeratometeric reading in the Phaco group preoperative k1= 43. 80, k 2= 44.69 and postoperative k1 =43.71and K2 =44.62.While Mean keratometeric reading in the SSTI group preoperative k1=44.00, K2 =45.02 and postoperative k1 =43.91 and K2= 45.41.Mean astigmatism at one month postoperative in patient undergoing Phaco was 1.3 ±0.9 and undergoingSSTI was 1.3± 0.7, there was no statistical difference in astigmatism at one month postoperative (P=0.5).This study reveals that superior approach in PHACO and MSICS produced similar astigmatic outcome,there is no significant difference in the mean surgically induced astigmatism in both types of surgery